Pengaruh Kepemimpinan Kepala Sekolah Berbasis Kearifan Lokal terhadap Sekolah Sehat Berorientasi Kebutuhan Siswa di Kabupaten Deli Serdang - Jumakir Jumakir; Hendriawan Hendriawan; Muhammad Ardansyah (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2025)
This study aims to examine the influence of school principals’ leadership grounded in local wisdom on the realization of healthy schools oriented toward students’ needs in Deli Serdang Regency. The research employed a quantitative approach with a cross-sectional correlational design. The population consisted of all public elementary and junior high school principals in Deli Serdang Regency, totalling 582 principals, from which 338 respondents were selected using stratified random sampling. Data were collected through structured questionnaires and analyzed using descriptive statistics and simple linear regression. The results indicate that both local wisdom–based principal leadership and healthy school conditions are categorized at a high level. Regression analysis reveals a strong and statistically significant relationship between local wisdom–based principal leadership and healthy schools (r = 0.756; R² = 0.572; p < 0.05), indicating that principal leadership contributes 57.2% to the realization of healthy schools. Among the leadership indicators, teachers’ intellectual stimulation emerges as the most dominant component influencing the creation of a safe, comfortable, and student-friendly school environment. This study concludes that local wisdom–based principal leadership plays a strategic role in supporting healthy schools oriented toward students’ needs. The findings highlight the importance of developing school leadership that is not only managerially adaptive but also capable of internalizing local cultural values in school management practices.